2011
DOI: 10.1038/ncb2346
|View full text |Cite
|
Sign up to set email alerts
|

USP15 is a deubiquitylating enzyme for receptor-activated SMADs

Abstract: The TGFβ pathway is critical for embryonic development and adult tissue homeostasis. On ligand stimulation, TGFβ and BMP receptors phosphorylate receptor-activated SMADs (R-SMADs), which then associate with SMAD4 to form a transcriptional complex that regulates gene expression through specific DNA recognition. Several ubiquitin ligases serve as inhibitors of R-SMADs, yet no deubiquitylating enzyme (DUB) for these molecules has so far been identified. This has left unexplored the possibility that ubiquitylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
174
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 32 publications
2
174
1
Order By: Relevance
“…However, it has also been shown that USP15 empowers transcriptional activation of R-SMADs, the ultimate effectors of the TGF-␤ pathway, by removing inactivating monoubiquitin (104); so fully discriminating the physiological importance of each of these effects may prove challenging. One consideration is that USP15 also promotes bone morphogenic protein (BMP) signaling, which utilizes overlapping SMAD family members with the TGF-␤ pathway, as effectors of an entirely distinct receptor type (104). USP11 was also identified as the major SMAD7 interacting DUB by proteomics and is proposed to be recruited to TGF-␤ receptor, which it deubiquitylates, in a similar manner to USP15 (6).…”
Section: Influence On Cell Physiology Through Control Of Receptmentioning
confidence: 99%
“…However, it has also been shown that USP15 empowers transcriptional activation of R-SMADs, the ultimate effectors of the TGF-␤ pathway, by removing inactivating monoubiquitin (104); so fully discriminating the physiological importance of each of these effects may prove challenging. One consideration is that USP15 also promotes bone morphogenic protein (BMP) signaling, which utilizes overlapping SMAD family members with the TGF-␤ pathway, as effectors of an entirely distinct receptor type (104). USP11 was also identified as the major SMAD7 interacting DUB by proteomics and is proposed to be recruited to TGF-␤ receptor, which it deubiquitylates, in a similar manner to USP15 (6).…”
Section: Influence On Cell Physiology Through Control Of Receptmentioning
confidence: 99%
“…SMAD1/5/8 and SMAD2/3 activation was measured by using pGL3-BMPresponsive element (BRE)-Luc and the pGL3-CAGA-Luc plasmids, respectively. 16 …”
Section: Luciferase Assaymentioning
confidence: 99%
“…Interestingly, the USP15 gene was found to be amplified in glioblastoma, breast cancer, and ovarian cancer, suggesting that enhanced TGFb signaling, as a consequence of USP15 overactivity, promotes progression of these tumors. USP15 has also been found to deubiquitylate monoubiquitylated R-Smads, promoting Smad activity (Inui et al 2011). In addition, USP11 has been shown to deubiquitylate TbRI and to enhance TGF-b signaling (Al-Salihi et al 2012).…”
Section: Tgf-b Receptors Are Regulated By Ubiquitylation Sumoylationmentioning
confidence: 99%